Prevalence of Risk Factors for Coronary Artery Disease in the Brazilian State of Rio Grande do Sul - Gus,Iseu (2002)
OBJECTIVE - To determine the risk factors prevalence for coronary artery disease in the State of Rio Grande do Sul, Brazil and to identify their relation with the age bracket. METHODS - We carried out an observational, cross-sectional study of 1,066 adults older than 20 years in the Brazilian State of Rio Grande do Sul. We investigated the risk factors: familial antecedents, systemic arterial hypertension, high levels of cholesterol and glycemia, overweight/obesity, smoking and sedentary lifestyle. A standardized questionnaire completed at the patients' dwellings by health agents were used; the data were stored in an EPI-INFO software database. The results were expressed with a 95% confidence interval. RESULTS - The sample composition was of 51.8% females. The risk factors prevalences were: 1) sedentary lifestyle 71.3%; 2) familial antecedents: 57.3%; 3) overweight/obesity (body mass index >25): 54.7%; 4) smokers: 33.9%; 5) hypertension: 31.6% (considering >140/90mmHg) and 14.4% (considering >160/95mmHg); 6) high glycemia (>126 mg/dL): 7%; 7) high cholesterol >240 mg/dL): 5.6%. CONCLUSION - The prevalence of the major risk factors for coronary artery disease in the Brazilian state of Rio Grande do Sul could be determined in a study that integrated public and private institutions.